Rethinking 'Religious' Cognition: The Eliadean Notion of the Sacred in the light of the Legacy of Uno Harva - Anttonen, Veikko (Temenos, 2007)
The article discusses methodological similarities and differences between Uno Harva and Mircea Eliade, with the objective of reassessing the value of their comparativist programs for the study of religion in general and of 'religious' cognition in particular. The Finnish scholar Uno Holmberg-Harva (1882-1949) was a predecessor to Eliade as a scholar of Asian and European religious history. During the first three decades of the twentieth century, when the academic study of religion was still maturing in Europe, Harva expanded considerably the field of the ethnological study of religion with his religio-phenomenological monographs Der Baum des Lebens (1922), Finno-Ugric, Siberian Mythology (1927) and Die Religiösen Vorstellungen der Altaischen Völker (1938). Harva was a towering figure in Finnish scholarship. Originally a Protestant theologian and Lutheran minister, he resigned from his ecclesiastical position to become a historian of religion, field ethnographer, ethnosociologist and folklorist under the tutelage of Edward Westermarck and Kaarle Krohn. Harva's influence on the work of Eliade has been almost entirely ignorant by historiographers of Religious Studies.